2013
DOI: 10.1139/apnm-2012-0426
|View full text |Cite
|
Sign up to set email alerts
|

An examination of maternal contributors and potential modifiers of fetal growth in pregnancy

Abstract: A greater understanding of critical periods of body weight regulation, including pregnancy, may aid in efforts to optimize weight management strategies for the mother and her baby.The gestational period has been implicated to play, in the child, a vital role in the developmental origins of obesity and other cardiometabolic diseases later in life. Therefore, we initially examined existing literature on the role of maternal obesity and its link to pediatric obesity and documented the known underlying physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, no statistical tests were completed to determine if there were significant relationships between maternal characteristics and adverse outcome [ 1 , 11 , 12 ]. Maternal prepregnancy weight, body mass index (BMI), and nutrition/lifestyle issues were not reported in any of the five studies and are factors known to influence fetal growth [ 14 , 15 ]. Collectively, the definition of IABD is inconsistent and diagnostic thresholds varied between studies.…”
Section: Prenatal Ultrasound Markers and Identification Of Adversementioning
confidence: 99%
“…Furthermore, no statistical tests were completed to determine if there were significant relationships between maternal characteristics and adverse outcome [ 1 , 11 , 12 ]. Maternal prepregnancy weight, body mass index (BMI), and nutrition/lifestyle issues were not reported in any of the five studies and are factors known to influence fetal growth [ 14 , 15 ]. Collectively, the definition of IABD is inconsistent and diagnostic thresholds varied between studies.…”
Section: Prenatal Ultrasound Markers and Identification Of Adversementioning
confidence: 99%
“…Fourth, as demonstrated over the past century, intrauterine exposure to reduced maternal metabolic control has significant effects on the health and metabolic trajectories of offspring ( Freinkel and Goodner, 1962 ; Pedersen , 1967/1977 ; Whitelaw, 1977 ; Kervran et al, 1978 ; Catalano et al, 1998 , 2003 ; Aerts and Van Assche, 2006 ; Egeland and Meltzer, 2010 ; Catalano and Hauguel-De Mouzon, 2011 ; Adamo et al, 2012 ; Cisse et al, 2013 ; Ferraro, 2013 ). For example, in siblings discordant for intrauterine exposure to T2DM, Dabelea et al (2000 , p. 22208) demonstrated that exposure “conveys a high risk for the development of diabetes and obesity in offspring in excess of risk attributable to genetic factors alone” .…”
Section: The Lack Of Explanatory and Predictive Power Of Gene- And DImentioning
confidence: 99%